2017
DOI: 10.1093/sleep/zsx069
|View full text |Cite
|
Sign up to set email alerts
|

Sleep-Related Breathing Disorders in Chiari Malformation Type 1: A Prospective Study of 90 Patients

Abstract: This study confirms a high prevalence of SRBDs in patients with CM-1 and CM-1.5, with a predominant obstructive component. Nocturnal PSG recordings should be systematically conducted in these patients, especially those who are male, older, or overweight or those who present hydrocephalus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
26
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 64 publications
0
26
1
1
Order By: Relevance
“…The association between CM and SRBD has been reported in case reports, retrospective and prospective studies [9,[12][13][14][15][16]. They report a prevalence of SRBD in adults with CM1 ranging from 50 to 75% [9,[12][13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The association between CM and SRBD has been reported in case reports, retrospective and prospective studies [9,[12][13][14][15][16]. They report a prevalence of SRBD in adults with CM1 ranging from 50 to 75% [9,[12][13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…Mainly OSA and mixed sleep apnoea have been described in these cases. The prevalence of CSA and hypoventilation in these cases is less frequent [9,[13][14][15][16]. One study reported a prevalence of 57.6% for OSA and 15.4% for CSA in adults.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Sleep-disordered breathing, including obstructive sleep apnea, bradypnea, CSA, and hypoventilation, are described in pediatric and adult patients with ACM1; sleep-disordered breathing is not uncommon and has been reported in up to 50% to 75% of patients. 4,5 CSA is usually detected on polysomnography and may be the presenting sign of this underlying condition in an otherwise asymptomatic patient.…”
Section: Discussionmentioning
confidence: 99%
“…Аномалія Арнольда -Кіарі проявляється широким спектром симптомів, обумовлених складним патогенезом, і вони залежать від конкретного варіанта патології. При Кіарі 1 може розвиватися охриплість, параліч голосових зв'язок, дизартрія, дисфункція м'якого піднебіння, фарингеальна ахалазія, атрофія язика, аспірація, ністагм, центральне та обструктивне апное уві сні [1,8,14,15], осцилопсія, сенсоневральна глухота, синусова брадикардія, синкопе, гикавка, загальна слабкість, гіперрефлексія, позитивний симптом Бабінського, скандована мова, атаксія [16], головний біль, сколіоз [17], а також сенсорний і моторний неврологічний дефіцит, спричинений сирингомієлією.…”
unclassified